2017
DOI: 10.18632/oncotarget.20902
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as predictors for CNS relapse of systemic diffuse large B-cell lymphoma

Abstract: Systemic diffuse large B-cell lymphoma (DLBCL) is a potentially curable disease using current regimen of immunochemotherapy. Central nervous system (CNS) relapse is a complication that occurs in approximately 5% of DLBCL patients and is associated with a high fatality rate. Early identification of molecular markers for CNS involvement may serve for the highly needed accurate stratification of patients into risk groups regarding CNS relapse. MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The false discovery rate method was used to control multiple observations, and the adjusted P-value was used for further analysis. Fold-change difference were calculated for each comparison and the P-value was determined where P-value <0.05 was considered significant [28][29][30]. The miRNAs which showed significant expression level differences between BB and BA samples were selected for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The false discovery rate method was used to control multiple observations, and the adjusted P-value was used for further analysis. Fold-change difference were calculated for each comparison and the P-value was determined where P-value <0.05 was considered significant [28][29][30]. The miRNAs which showed significant expression level differences between BB and BA samples were selected for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of miR-30d is also found in Hodgkin lymphoma [48]. Besides, differentially expressed miR-30d is reported as a reliable biomarker candidate in CNS-DLBCL [49]. A previous study has reported the downregulation of let-7e in DLBCL compared to normal lymph nodes whereas the reduced expression of let-7g shows a good event-free survival [50].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the plasma level of miR-93 is associated with higher mortality in 25 patients with lymphoma [44], which suggests that they are reliable biomarker candidates. Differentially expressed miR-30d is also predicted for CNS-DLBCL [45]. Although the data is limited by the small sample size and there is less evidence for the above-mentioned function and signaling pathways at present, it would help us to better understand biological significances of the CNS signature of miRNAs in PCNSL.…”
Section: Discussionmentioning
confidence: 99%